KONSTRUKSI MAKNA BAGI WANITA PENGGUNA VAPE DI KOTA PEKANBARU - Nofrianto Arifin; Muhammad Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Woman consider themselves the same as men, where they are adept at using vape. The development of the trend gives curiosity as well as the aroma generated from the liquid or steam provides a sense of enjoyment in terms of vape taste is very different from conventional cigarettes generally. The study aims to determine the motives of female users of vape, the meaning of female users of vape and experience communication woman users vape.This research using phenomenology approach and taking informant using snowball technique with key informant. This study has 5 informant. With data collection techniques such as observation, interview adn documentation. While for the technique of examination of data validity, writer use technique of extension of participation. The data obtained are then processed for reduction, presented until a general conclusion is produced.The result of this study show that 1The motive of women vape users divided into two motives because (because motive) the sense of comfort and environmentally friendly, while the motive for (in order to motive) the sense of desire to quit smoking and the growth of confidence. 2The meaning of female users of vape that is as an upper middle class cigarette, reduce the number of early smokers (under age), reduce smoking addicts (quit smoking), various flavours (aroma) and various forms of vape and cigarettes hits (kekinian). 3The experience of woman communication vape users divided into two pleasant communication experience where a new friend, exclamation and race to form the creation of the vape steam, and upleasant communication experience that is considered naughty girl. Naughty girl here can be interpreted as a person who can not be arranged to do as he pleased only, doing according to his will. And has no moral and ethical and is considered cynical (worth hating). Have no moral can be interpreated as people who have no religious value (less), are often considered like a child’s night because the habit is only done people who are far from religion.